Supporting Collaborative Privacy-Observant Information Sharing Using RFID-Tagged Objects - Shin'ichi Konomi; Chang S. Nam (Advances in Human-Computer Interaction)
RFID technology provides an economically feasible means to embed computing and communication capabilities in numerous physical objects around us, thereby allowing anyone to effortlessly announce and expose varieties of information anywhere at any time. As the technology is increasingly used in everyday environments, there is a heightening tension in the design and shaping of social boundaries in the digitally enhanced real world. Our experiments of RFID-triggered information sharing have identified usability, deployment, and privacy issues of physically based information systems. We discuss awareness issues and cognitive costs in regulating RFID-triggered information flows and propose a framework for privacy-observant RFID applications. The proposed framework supports users' in situ privacy boundary control by allowing users to (1) see how their information is socially disclosed and viewed by others, (2) dynamically negotiate their privacy boundaries, and (3) automate certain information disclosure processes.